Developmental lead exposure and aggression in male rats: Influences of maternal care and environmental enrichment - Shamaila Zafar; Courtney Williams; Jaehyun Joo; Blanca E. Himes; Jay S. Schneider (Toxicology Reports)
Developmental lead (Pb) exposure results in a variety of cognitive deficits and behavioral issues including increased antisocial behavior and aggression. This study investigated the effect of developmental Pb exposure on aggression and violent behavior in male rats and the potential modulatory influences of quality of maternal care and enriched/non-enriched housing conditions. Long-Evans male rats with or without Pb exposure (perinatal or early postnatal) from low or high maternal care mothers (based on amounts of licking/grooming and arched-back nursing) were randomly assigned to live in enriched or non-enriched environments at weaning. At postnatal day 120–190, offensive aggression was assessed using a resident intruder test. Clinch attack (CAK) frequency and latency, and occurrence of biting events were observed to determine violent behavior. Both perinatal and postnatal Pb-exposed rats were significantly more aggressive and showed more violent behavior, compared to non-Pb-exposed animals, regardless of level of maternal care and environmental enrichment. High maternal care significantly lowered the proportion of animals with short CAK latencies and enriched housing significantly lowered the occurrence of biting events. These results suggest that high maternal care and enriched housing may potentially modify expression of violent aggressive behavior in rats with early life Pb exposure.